2016
DOI: 10.4103/0972-9941.186690
|View full text |Cite
|
Sign up to set email alerts
|

Single-access laparoscopic approach in the surgical treatment of endometrial cancer: A single-institution experience and review of literature

Abstract: BACKGROUND:The aim of this study was to assess the surgical and oncological outcome for the management of endometrial cancer (EC) by laparoendoscopic single-site surgery (LESS).PATIENTS AND METHODS:We performed a retrospective chart review of patients who underwent a LESS for EC. All the patients were treated by the same surgical team between July 2009 and June 2013 at the Gynaecologic Oncologic Unit, Regina Elena National Cancer Institute, Rome, Italy.RESULTS:A total of 50 women were included, with a median a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…However, we found that there were no significant difference in these characteristics of patients. As some studies reported that disease features and patients’ features would not been the limitation of LESS 25. Song et al 26 successfully performed LESS for ovarian cysts with a minimal diameter at less 15 cm with few complications occurred and they concluded that the size is not a necessary contraindication for LESS of ovarian masses.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that there were no significant difference in these characteristics of patients. As some studies reported that disease features and patients’ features would not been the limitation of LESS 25. Song et al 26 successfully performed LESS for ovarian cysts with a minimal diameter at less 15 cm with few complications occurred and they concluded that the size is not a necessary contraindication for LESS of ovarian masses.…”
Section: Discussionmentioning
confidence: 99%